PENERAPAAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IX.4 SMP NEGERI 21 PEKANBARU - Novita Rasta Rasta; Zuhri. D '; Elfis Suanto Suanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research was based on the students’ achievement in learning mathematics especially grade IX.4 of SMPN 21 Pekanbaru under the Mastery Minimum Criteria with percentage of 27,77%. The subject of basic competence were about triangle. The teacher-centered learning was still used to teach materials during the learning process. The research conducted was the Classroom Action Research. The aims of this research is to improve the learning process and results on the students learning mathematic by implementing cooperative learning model structural approach of Think Pair Square. There were 36 students in the class consisting 13 boys and 23 girls as the participant of this research. The instruments of data collection in this research were observation sheets and students Mathematic tests. The observation sheets were analyzed in qualitative desciptive, while the students’ Mathematic tests were analyzed in quantitative desciptive. The qualitative desciptive showed an improvement of learning process prior to the action on the first and second cycles. The results of this research showed an increasing number of students learning Mathematic from the basic score with percentage 27,77% to 36,11% on the first test and 50% on second test. Based on the result of this research could be concluded that the implementation of Cooperative Learning Model structural approach of Think Pair Square can improve the students’ achievement of learning Mathematic in grade IX.4 of SMPN 21 Pekanbaru in the first semester academic years 2014/2015. Key Word : Students’ Math Achievement, Cooperative Learning Model Structural Approach of Think Pair Square, Clasroom Action Research